2014
DOI: 10.1186/1471-2458-14-654
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and demographic factors are associated with dietary patterns in a cohort of young Brazilian adults

Abstract: BackgroundThe aim of the present study was to identify the main dietary patterns among young adults and to investigate the association of socioeconomic and demographic factors, and social mobility with dietary patterns.MethodsData from the fourth follow-up of the 1978/79 Ribeirão Preto birth cohort study, Brazil, were used. A total of 2,061 young adults, whose mothers gave sociodemographic information at birth in 1978–79, provided sociodemographic and dietary data through a validated food frequency questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
52
0
18

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 35 publications
24
52
0
18
Order By: Relevance
“…Non-white women presented a higher probability of adherence to the Brazilian DP. These data corroborate other Brazilian studies that investigated both genders 37,38 . According to Arruda et al 37 , what could explain this result is the fact that beans, the most characteristic food of these patterns, were the main components of the diet of people of low socioeconomic status in the colonial period in Brazil.…”
Section: Discussionsupporting
confidence: 92%
“…Non-white women presented a higher probability of adherence to the Brazilian DP. These data corroborate other Brazilian studies that investigated both genders 37,38 . According to Arruda et al 37 , what could explain this result is the fact that beans, the most characteristic food of these patterns, were the main components of the diet of people of low socioeconomic status in the colonial period in Brazil.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, the "fruit and vegetables" and "low sugar/low fat" patterns were more frequent among women, confirming the results of other studies in which consumption of healthy foods is reported more frequently by women and older adults 38,42 . Probably because of their greater concern with beauty, health and more frequent recourse to health services, these two sub-groups are more likely to be following specific recommendations for control of diabetes, dyslipidemias and weight control 43,44,45 .…”
Section: Discussionsupporting
confidence: 87%
“…The distribution of those patterns by sociodemographic characteristics of the ELSA-Brasil study population is similar to recent findings in the Brazilian literature. Although using different methods, Gimeno et al 37 observed greater frequency of the "healthy" pattern among women and older adults, while Marchioni et al 13 and Arruda et al 38 observed higher frequencies of the traditional pattern among men and among individuals with less schooling.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary patterns were further dichotomized to compare the highest quartile to the other three (i.e. highest quartile vs. others) (Arruda et al 2014). …”
Section: Methodsmentioning
confidence: 99%